Experimental investigation and optimization of multiple performance characteristics of Al-Mica-B4C hybrid reinforced composite in drilling operation. (2018) - Narale, M.N.; Kulkarni, S.G.; Menghani, J.V.; Lal, Achchhe
Abstract: Machining of composite is critical task and many parameters are needed to study in order to evaluate the performance of composite. In present study, performance characteristics of Al- mica-B4 C composite are evaluated and optimized with Taguchi-grey relational analysis in drilling of B4 C and mica reinforced hybrid aluminium matrix composites (AMCs) manufactured by powder metallurgy process. HSS, TiAlN coated carbide drill bits and uncoated cementide carbide drills bits were used under dry cutting conditions. The drilling parameters such as feed rate, spindle speed, drill tool material and material parameters like wt. % of B4C as well as Mica particles were optimized based on multiple performance characteristics including thrust force, drilling torque and surface roughness. Experiments were conducted on a computerised numerically controlled vertical machining centre. Drilling tool dynamometer is used to measure the thrust force and drilling torque. Also, to measure the surface roughness of drilled hole portable surface roughness tester is used which shows the readings in microns. Microstructure of composites and surface morphology of drilled hole is studied by using optical microscopy. Finally, it is concluded that, among the drilling tools used, TiAlN coated carbide drill bit shows the better result than other drill bits used. Composites manufactured in present study shows better strength for all levels of reinforcement. Also, it is found that the drilling feed rate affects on the drilling process significantly.